Effect of Arnebia Euchroma poultice on the prevention of peripheral intravenous catheter-related phlebitis: A randomized clinical trial - Shokoh Varaei; Bahareh Ghafourzadeh Toomatari; Mohammad Kamalinejad; Mir Saeed Yekaninejad; Fariba Sadat Kazemi; Ebrahim Khadem (Tehran University of Medical Sciences, 2018)
Background & Aim: The most common complication of peripheral intravenous catheter use is phlebitis. This study aimed to determine the effect of Arnebia Euchroma on the prevention of peripheral intravenous catheter-related phlebitis. Methods & Materials: A double-blind randomized clinical trial done on 120 patients hospitalized in CCU and heart wards of Shariaty hospital in Tehran in 2017. The convenience samples were allocated into the two groups of control and intervention. After the insertion of an IV catheter (by sterile technique, in the site of upper limb without any signs of phlebitis), Arnebia Euchroma poultice for the intervention group and placebo poultice for the control group, was applied to the skin in the distal portion of IV catheter at 3×3 cm from the catheter insertion site. Then, this site was covered by sterile dressing. The patient was monitored every 12 hours by removing the dressing, and the poultice was applied again. Data were analyzed by descriptive and inferential statistics using the SPSS software. Results: The two groups were homogeneous in terms of age and sex, but were different in the number of hospitalization days. While no phlebitis was observed in the baseline, there was a significant difference between the two groups (42.37% for intervention group vs 0% for control group) at the hour of 12. By adjusting the effect of hospitalization days, the difference was still significant (P<0.001). Conclusion: Arnebia Euchroma poultice was effective in the prevention of phlebitis. Thus, this poultice can be used when inserting a peripheral intravenous catheter. Clinical trial registry: IRCT2017012432147N1